Moisture sorption characteristics of Rasomalai at different temperatures - Khojare, Ajit (Indian Journal of Dairy Science, 2021)
The sorption characteristics of rasomalai were measured at the temperatures of 20oC, 30oC, and 40oC and in the water activity range of  0.11 - 0.97.   The isotherm exhibit sigmoid shape and correspond to type  II. In rasomalai, at all water activities values of equilibrium moisture content decreased with an increase in temperature. However, a clear cut inversion was observed intermittently at 30oC and 40oC.  The BET and GAB equation fitted hold good as indicated by the statistical values R2, P and %RMS.   The BET  monolayer value in rasomalai decreased from 5.11g of water/100g of solids at 20oC to to 3.80 g of water/100 g of solids at 40oC.  The GAB monolayer value for  rasomalai decreased from 5.04 g of water/100 g of solids at 20oC to 3.86 g of water/100 g of solids at 40oC.  The Caurie equation was used to determine properties of sorbed water viz., density of sorbed water, number of adsorbed monolayers, bound or non freezabe water and surface area of sorption in rasomalai.  The net isosteric heat of sorption in rasomalai ranged from 58.24 kJ/mol at 6.63 % moisture content to 0.44 kJ/mol at 32.75 % moisture content.